Studi Kinerja Pemasaran Edel Cacao: Peran Kualitas Produk dan Harga - Lestari, Retno Cahyaningtyas Puji; Juniarti, Rosa Prafitri (Jurnal Ilmu Manajemen, 2020)
This study aims to investigate the marketing mix impact of product quality and prices on sales performance which is decomposed into the volume of sales, the volume of consumers, and volume bought each consumer, using longitudinal data. This study analyzes the decline sales phenomenon of Edel Cocoa in PT Perkebunan Nusantara XII (Persero) for five years in a row from 2014-2018 through the implementation strategy of product quality and price, with total 253 products sold and 241 consumer purchase transactions. Using three generalized estimating equations method at the real level (?) = 5%. The result indicates that the marketing mix of product quality and prices have a strong impact on sales volume and volume bought each consumer. However, the marketing mix of product quality and prices don't have a significant impact on the volume of consumers. The marketing mix of quality products and prices simultaneous in explaining sales performance is at 14.5% while the remaining 85.5% is explained by other factors not included in this research model.